Kreativitas Guru PAI dalam Mengembangkan Bahan Ajar di SD Negeri 105280 Desa Lama - Suci Lailannaz; Rustam R; Muhammad Rapono (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This research aims to determine the creativity of Islamic religious education teachers in developing teaching materials and to find out what factors support and inhibit the creativity of these teachers in developing teaching materials in order to increase student activity. This research uses a qualitative research method using a descriptive approach, where the data that researchers collect is in the form of words or images that are obtained directly without using numbers and actually occur naturally (natural setting), the data and facts found are then analyzed and explained so that they are easy to understand. By other people. Data collection techniques use observation, interviews and documentation. The data analysis techniques used in this research are data reduction, data presentation and drawing conclusions. The results of the research show that the creativity of Pai teachers in developing teaching materials is quite good. Because pai teachers are able to utilize learning media to create an interesting and motivating learning atmosphere for students. PAI teachers’ creativity in developing teaching materials is influenced by several supporting factors, namely: School infrastructure, support from the principal and colleagues and good enough classrooms. So PAI teachers can increase their creativity in improving student learning.